Prevalence and contamination patterns of Listeria monocytogenes in Pleurotus eryngii (king oyster mushroom) production plants - Xu, Jiang; Wu, Shi; Liu, Ming; Xiao, Zitian; Peng, Yangyang; He, Huanqing (Frontiers in Microbiology, 2023)
Listeria monocytogenes is a major foodborne pathogen that is well-known for its high mortality rate upon infection. In recent years, the edible mushroom has also been found to be an important source of L. monocytogenes, but the contamination sources in Pleurotus eryngii (the king oyster mushroom) were unclear. In this study, a total of 203 edible mushrooms and environmental samples from four P. eryngii production plants were obtained. As a result, 29 samples (14.3%) were positive for L. monocytogenes, including eight mushroom samples (13.3%, 8/60) and 21 associated environmental samples (14.7%, 21/143). The contamination of L. monocytogenes in plants A and B was more severe and was likely to originate from the mycelium stimulation machine. The isolates belonged to serogroups II.1 (4b-4d-4e), I.1 (1/2a-3a), and I.2 (1/2c-3c), and multilocus sequence typing (MLST) revealed that these L. monocytogenes strains belonged to five different sequence types (ST3, ST121, ST9, ST87, and ST224). The ST121 and ST3 isolates were only found in plants A and B, respectively. The isolates were carried by hly (29/29, 100%), inlB (23/29, 79.3%), inlA (29/29, 100%), inlC (29/29, 100%), inlJ (29/29, 100%), actA (19/29, 65.5%), iap (29/29, 100%), plcA (26/29, 100%), plcB (29/29, 100%), prfA (27/29, 93.1%), and mpl (29/29, 100%). Further study of inlA sequencing showed that 65.5% of strains (19/29) contained full-length InlA that was required for host cell invasion, whereas the mutation led to premature stop codons (PMSCs) at position 492 (type 6) on inlA alleles. All isolates in this survey were sensitive to gentamicin, kanamycin, sulbactam/ampicillin, trimethoprim-sulfamethoxazole, tetracycline, and doxycycline. The drug with the highest resistance is rifampicin (37.9%), followed by penicillin (24.1%) and ciprofloxacin (10.3%). Most multiply resistant strains are isolated from raw materials and equipment of the P. eryngii processing lines. Our study reflects the contamination patterns and potential risk of L. monocytogenes infection in P. eryngii production plants. The persistence of specific L. monocytogenes isolates (such as ST121 and ST3) may assist with contamination. In accordance with these results, the control of L. monocytogenes should focus on the environmental materials, especially in the mycelium stimulation stage. However, effective Listeria monitoring programs will allow for the improved development of Listeria control measures to minimize cross-contamination in the processing of P. eryngii.